New Rates from New Weights. (IMF Working Papers; Working Paper ;, 2005)
This paper describes the result and the methodology of updating nominal and real effective exchange rate weights on the basis of trade data over 1999-2001. The underlying framework is an updated version of the IMF's current effective exchange rate calculation, which uses weights largely based on 1989-91 data. Since then, substantial changes have occurred in international trade relations, warranting a recalculation of effective exchange rate indices on the basis of new trade patterns. Updated weights show that the United States and developing countries (most notably China) have grown in their importance in global trade, while Japan and the European Union have declined, with substantial implications for the path of the dollar and exchange rate effects of emerging market crises since 1995.